(untitled) (Bangladesh Journal of Animal Science, 2012)
Effect of feed supplementation to does grazed on naturally grown grasses during pre-partum on growth, reproduction and lactation performances of does and growth of the kids were investigated. Fifteen two-toothed and non-pregnant does of about one and half year of age constituted the experimental animals which were randomly allocated in the three groups of 5 and offered A) grazing ad libitum + l00g Mashkalai + 100g Wheat bran, B) grazing ad libitum + 50g Mashkalai + 50g Wheat bran and C) grazing ad libitum. The dry matter intake (DMI) between supplemented groups of A and B were almost similar (90 and 89g/kg w0.75/d respectively) and 12% higher than the control group C (80g/ kg w0.75/d). This DMI represent 4.6, 4.5 and 4.1% of live weight for group A, B and C, respectively. Does in treated group A consumed 30 and 62% more CP than group B and control group C, respectively. Similarly, group B consumed about 25% more CP than group C. There was no effect of grazing and supplementation before the pre-partum period on milk yield between treated group (A and B) and control group C (Av. 157 ml and 156 ml/d, respectively), rearing rate and growth of the suckling kids. Present study suggests that provision of grazing and supplementary feeding increases nutrients intake of does but appear to have no influence on milk yield. Higher prolificacy of Black Bengal goat may not bring any benefit unless milk production is increased. http://dx.doi.org/10.3329/bjas.v41i1.11975